Green growth, what challenges for the countries of the West African Economic and Monetary Union ? - (:unkn) unknown (My University, 2013)
On November 13 and 14, 2013, the West African Development Bank (BOAD) commemorated its 40th anniversary. An international conference was organized on this occasion. This communication was made within the framework of thematic session 3 "Green growth, what challenges for the countries of the West African Economic and Monetary Union (WAEMU)", page 9 of the proceedings. Its theme was "opportunities, areas and means of solar energy development in the West African Economic and Monetary Union". It lists the opportunities, areas, means of development and the challenges of these new markets for BOAD and WAEMU.
Keywords: African Research